2009
DOI: 10.2478/v10026-009-0025-y
|View full text |Cite
|
Sign up to set email alerts
|

The effect of hydrotropes on the solubility and mass transfer coefficient of 2-nitrobenzoic acid

Abstract: The effect of hydrotropes on the solubility and mass transfer coefficient of 2-nitrobenzoic acid A comprehensive investigation on the solubility and mass transfer coefficient enhancement of 2-nitrobenzoic acid through hydrotropy, has been undertaken. The solubility and mass transfer coefficient studies were carried out using hydrotropes such as sodium acetate, citric acid and nicotinamide under a wide range of hydrotrope concentrations (0 to 3.0 mol/L) and different system temperatures (303 to 333 K). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2010
2010
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Hydrotropic solutions don't really exhibit colloidal tendencies and suggest a weak interaction between the hydrotropes and the molecule of solute 37. Hydrotropes are generally water-soluble and surface-active compounds that can significantly improve the solubility of organic solvents such as esters, acids, alcohols, aldehydes, ketones, hydrocarbons and fats [38][39][40][41] .…”
Section: Bcs Classification Systemmentioning
confidence: 99%
“…Hydrotropic solutions don't really exhibit colloidal tendencies and suggest a weak interaction between the hydrotropes and the molecule of solute 37. Hydrotropes are generally water-soluble and surface-active compounds that can significantly improve the solubility of organic solvents such as esters, acids, alcohols, aldehydes, ketones, hydrocarbons and fats [38][39][40][41] .…”
Section: Bcs Classification Systemmentioning
confidence: 99%
“…The effectiveness of a hydrotrope’s dissolving capability is mainly dictated by the size of the hydrophobic part and only to a lesser extent by the presence of a charge on the hydrophilic part . Stacking of hydrotropes in water by π–π interactions or dipole–dipole interactions has been identified as the root cause of their solubilizing power. How hydrotropic dissolution occurs is still unclear but may have to do with (i) the hydrotrope’s self-aggregation potential, , (ii) kosmotropic/chaotropic properties, , and (iii) the ability to form micelle-like structures. , …”
Section: Introductionmentioning
confidence: 99%
“…The effect of hydrotropes on the solubility and mass transfer coefficient for a series of organic acids and esters such as salicylic acid, 2-nitrobenzoic acid, butyl acetate, ethyl benzoate, amyl acetate, methyl salicylate, and benzyl acetate was studied in our earlier publications. It has been observed that, in many two-phase reaction systems involving a sparingly soluble organic compound like stearic acid, the mass transfer coefficient was found to be very low solely due to the poor solubility of stearic acid in the aqueous phase. Since stearic acid serves as a raw material/intermediate for a wide variety of chemicals and allied products and the separation of stearic acid from any liquid mixture seems to be difficult, this hydrotropic technique can be adapted to increase the solubility as well as to separate such mixtures effectively.…”
Section: Introductionmentioning
confidence: 99%